Diversity and ethnobotanical study of medicinal plants in Ban Hua Kua, Kae Dam District, Thailand - WILAIJIT NUMPULSUKSANT; Surapon Saensouk; Piyaporn Saensouk (Society for Indonesian Biodiversity, 2021)
Abstract. Numpulsuksant W, Saensouk S, Sanesouk P. 2021. Diversity and ethnobotanical study of medicinal plants in Ban Hua Kua, Kae Dam District, Thailand. Biodiversitas 22: 4349-4357. Diversity and ethnobotanical study of medicinal plants in Ban Hua Kua village, Kae Dam District, Maha Sarakham Province, Thailand. Biodiversitas 22: xxxx-xxxx. This study can serve as basic information for further study and provide conservation criteria for medicinal plants in Ban Hua Kua village, Kae Dam District, Maha Sarakham Province to assure continued species richness and sustainable use. This study aimed to document ethnobotanical knowledge of medicinal plants, including their diversity, in Ban Hua Kua village, Kae Dam District, Maha Sarakham Province, Thailand. The ethnobotanical data were obtained from 19 local experts using semi-structured forms to record the interviewee's personal information and topics related to the medicinal use of specific plants. Thirty-eight medicinal plants belonging to 35 genera in 23 families were collected. The most commonly represented family was Zingiberaceae comprised of six species (Alpinia galanga (L.) Willd., Boesenbergia rotunda (L.) Mansf., Curcuma angustifolia Roxb., Curcuma comosa Roxb., Curcuma longa L., and Zingiber officinale Roscoe), followed by Fabaceae with four species (Derris scandens (Roxb.) Benth., Dialium cochinchinense Pierre, Senna siamea Lam., and Tamarindus indica L.), and Rutaceae with three species (Aegle marmelos (L.) Corrêa ex Roxb., Clausena wallichii Oliv., Hesperethusa crenulata (Roxb.) Roem.), while the other 20 families represent only one to two plant species. The root was the most frequently used part of the plant. The species with the highest use-value was Antiaris toxicaria Lesch. (0.68), a native plant of the Ban Hua Kuavillage. Diospyros mollis Griff. (CI = 0.21), Dialium cochinchinense Pierre (CI = 0.21), Anisomeles indica (L.) Kuntze (CI = 0.21), Vitex glabrata R. Br. (CI = 0.21), Aegle marmelos (L.) Corrêa ex Roxb. (CI = 0.21), Phyllanthus emblica L. (CI = 0.21), and Hesperethusa crenulata (Roxb.) Roem. (CI = 0.21) were found the highest cultural important index (CI), while Diospyros mollis Griff., Dialium cochinchinense Pierre, Anisomeles indica (L.) Kuntze, Vitex glabrata R. Br., Phyllanthus emblica L., Aegle marmelos (L.) Corrêa ex Roxb., and Hesperethusa crenulata (Roxb.) Roem. were found the highest %FL = 50. The climber was mostly used for medicinal plants (IAR = 0.97). Root (57.89%), leaf (52.63%), and fruit (39.47%) were reported the most plant parts used by the villagers. Therefore, the indigenous knowledge of medicinal plants at Ban Hua Kua village is indicated to conservation for sustainable use in the future. Moreover, this study was the first reported in Maha Sarakham province.